Breakfast with Einstein : the exotic physics of everyday objects - Orzel, Chad (BenBella Books, Inc., 2018)
Orzel, author of How to Teach Quantum Physics to Your Dog, explores how quantum connects with everyday reality, and offers engaging, layperson-level explanations of the mind-bending ideas central to modern physics.--